Does Serum Vitamin D Level Affect COVID-19 Infection and Its Severity?-A Case-Control Study. (10th November 2021) - Ye, Kun; Tang, Fen; Liao, Xin; Shaw, Benjamin A.; Deng, Meiqiu; Huang, Guangyi; Qin, Zhiqiang; Peng, Xiaomei; Xiao, Hewei; Chen, Chunxia; Liu, Xiaochun; Ning, Leping; et al.
Abstract: Background: As effective medication to treat COVID-19 is currently unavailable, preventive remedies may be particularly important. Objective: To examine the relationship between serum 25-hydroxy vitamin D (25(OH)D) level and COVID-19 infection, its severity, and its clinical case characteristics. Methods: This case-control study compared serum 25(OH)D levels and rates of vitamin D deficiency (VDD) between 80 healthy controls and 62 patients diagnosed with COVID-19 and admitted to Guangxi People's Hospital, China, 2/16/2020–3/16/2020. Cases were categorized into asymptomatic, mild/moderate, and severe/critical disease. Logistic regression analysis was conducted to examine the associations between 25(OH)D level, or VDD, and case status/severity of COVID-19 while controlling for demographics and comorbidities. A threshold level of vitamin D for conveying COVID-19 risk was estimated. Results: Severe/critical COVID-19 cases were significantly older and had higher percentages of comorbidity (renal failure) compared to mild cases. The serum 25(OH)D concentration in COVID-19 patient was much lower than that in healthy control. And 25(OH)D level was the lowest in severe/critical cases, compared with mild cases. In further, significantly higher rates of VDD were found in COVID-19 cases (41.9%) compared to healthy controls (11.1%). And VDD was the greatest in severe/critical cases (80%), compared with mild cases (36%). These statistically significant associations remained even after controlling for demographics and comorbidities. A potential threshold of 25(OH)D (41.19 nmol/L) to protect against COVID-19 was identified. Conclusion: Elderly and people with comorbidities were susceptible to severe COVID-19 infection. VDD was a risk factor for COVID-19, especially for severe/critical cases. While further confirmation is needed, vitamin D supplementation may have prevention or treatment potential for COVID-19 disease.